Retirement and cognitive abilities - Alberto Tumino (University of Essex, Institute for Social and Economic Research (ISER), 2016)
This paper investigates how retirement influences the cognitive abilities of British older workers. The analysis employs data from Understanding Society and relies on an instrumental variable approach to address endogeneity bias. Consistent with the "use it or lose it" hypothesis, we show that retirement induces cognitive decline, although the relationship is weaker for women employed in routine occupations. Disregarding potentially offsetting effects on other dimensions of health, we conclude that extending the working life has a beneficial effect on the cognitive capital of older workers and that maintaining a mentally engaging and stimulating life-style during retirement contributes to the cognitive health of the mature population.
Keywords: J26; J14; 330; cognitive abilities; retirement; state pension age